Secretors in Manipuri Population: A Study - Devi, A Sylvia; Meera, Th; Singh, Kh Pradipkumar; Nabachandra, H; Shah , Ibungo (Journal of Indian Academy of Forensic Medicine, 2015)
The term ‘secretor’ is used for an individual who secretes ABO blood group antigens in body fluids such as saliva, sweat, tears, gastric juice, semen, urine, etc. The present study has been taken up to find out the distribution of secretors and non-secretors in the Manipuri population. In this study, saliva samples from 400 individuals, 213 males and 187 females who were in the age group of 15 to 60 years were collected, and the samples were examined by haemagglutination inhibition technique. The samples were also examined at different time intervals from the time of collection of samples. The findings were entered in proforma and statistically analyzed. It is observed that 49.5% of the Manipuri subjects in this study are secretors and 50.5% are non-secretors. The percentage of agglutinins is the highest in the blood group ‘O’. The ABO group antigens can be detected from the saliva of secretors up to 180 days or 6 months from the time of collection of samples. A relatively higher number of people in the Manipuri population are non-secretors and the percentage of agglutinins is highest in blood group ‘O’.